2014
DOI: 10.1097/pcc.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Health Outcomes in the PICU

Abstract: Objectives Reports of the burden of hypertension in hospitalized children are emerging, but the prevalence and significance of this condition within the pediatric intensive care unit (PICU) are not well understood. The aims of this study were to validate a definition of hypertension in the PICU and assess the associations between hypertension and acute kidney injury (AKI), PICU length of stay (LOS), and mortality. Design and Setting Single center retrospective study using a database of PICU discharges betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(33 reference statements)
0
12
0
1
Order By: Relevance
“…Hypotension is a common cause of renal hypoperfusion leading to acute tubular necrosis. The diagnosis is suspected when AKI develops after a hypotensive event, severe sepsis, or drug exposure and is distinguished from prerenal AKI by laboratory testing and response to volume expansion (28). Interestingly; it was observed that hypertension in PICU children was associated with AKI (29).…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension is a common cause of renal hypoperfusion leading to acute tubular necrosis. The diagnosis is suspected when AKI develops after a hypotensive event, severe sepsis, or drug exposure and is distinguished from prerenal AKI by laboratory testing and response to volume expansion (28). Interestingly; it was observed that hypertension in PICU children was associated with AKI (29).…”
Section: Discussionmentioning
confidence: 99%
“…That is to say if the SCr rose from 0.1 to 0.2 mg/dL or from 0.1 to 0.4 mg/dL each did not qualify as AKI (SCr was not above 0.5 mg/dL), but if the SCr rose from 0.4 to 0.6 mg/dL or from 0.3 to 0.6 mg/dL this did qualify as AKI (SCr was above 0.5 mg/dL). This was utilized to account for the precision of our assay locally and has been utilized successfully in previous reports [18][19][20] to prevent a bias toward classifying AKI as present in young infants [21]. A modified Jaffe reaction is utilized for SCr measurement at the University of Michigan.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…The more conservative estimates come from studies where the diagnosis was established retrospectively, based on a billing code diagnosis of HTN at discharge; the more liberal estimates are from studies using single emergency room admission BP measurements [ 13 , 14 ]. Studies suggest that critical illness is a risk factor for acutely elevated BP; Ehrmann et al [ 15 ] found the prevalence of HTN to be 25% among pediatric ICU patients when defining HTN as at least three SBP and/or DBP readings above the 99th percentile over 1 day. Most importantly, this study correlated HTN using this definition to clinical outcomes such as increased odds of acute kidney injury and increased length of stay [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that critical illness is a risk factor for acutely elevated BP; Ehrmann et al [ 15 ] found the prevalence of HTN to be 25% among pediatric ICU patients when defining HTN as at least three SBP and/or DBP readings above the 99th percentile over 1 day. Most importantly, this study correlated HTN using this definition to clinical outcomes such as increased odds of acute kidney injury and increased length of stay [ 15 ].…”
Section: Discussionmentioning
confidence: 99%